Perilaku Masyarakat di Ruang Terbuka Publik Alun-Alun Kabupaten Blora - Septyani Wahyu Pradani; Nurini Nurini (TATALOKA, 2020)
The existence of public open spaces in the city center can be used to improve the quality of the environment and social relations of the community. Community social relations can be seen from the interaction between individuals in using space that shapes behavior patterns. Thus, the development of public space can be seen from the behavior of the people around. Blora District Square is one of the public open spaces in the center of Blora Regency, which has an important role as a provider of socio-cultural space to accommodate various kinds of community activities. To determine the effect of providing space on visitor behavior, it is necessary to conduct research on community behavior in Blora District Square. This study aims to identify community behavior in using Blora District Square as a public open space. The analysis in this study consisted of visitor characteristics, activity characteristics, movement patterns, and behavior analysis. The method used in this study is descriptive quantitative and qualitative methods with descriptive statistical and Behavior Setting analysis techniques. Behavior Setting analysis is used to determine the movement pattern with place-centered mapping and person-centered mapping techniques. The subject of this study is the user of Blora Regency square. The sampling technique used is Probability Sampling. The results of this study are expected to provide recommendations related to the improvement of the quality of space in Blora Regency square in order to form better behavior patterns.